TINJAUAN STANDAR ETIKA GLOBAL TERHADAP REGULASI TEKNOLOGI INFORMASI DI INDONESIA: PERSPEKTIF PAPA FRAMEWORK DAN HUKUM POSITIF - Evy Nurmiati; Salsabila Nursalima (CV. Denasya Smart Publisher, 2026)
The exponential growth of information technology (IT) demands alignment between national legal regulations and global ethical standards. This study critically examines the extent to which Indonesia's positive law adopts global ethical standards through the lens of the PAPA Framework (Privacy, Accuracy, Property, Accessibility) and the five fundamental principles of cyber ethics. Employing a normative legal research method combined with comparative literature review, this study analyzes international codes of ethics (ACM and IEEE) alongside Indonesia's domestic regulations, including the Electronic Information and Transactions Law (UU ITE), the Copyright Law, the Personal Data Protection Law (UU PDP), and the Second Amendment to the UU ITE. The findings indicate that Indonesia's positive law has accommodated privacy, accuracy, and property as a legal floor, with notable reinforcement of the privacy pillar following the enactment of the UU PDP. However, a significant gap remains in the accessibility dimension and in practical ethical implementation, as reflected in the prevalence of dark patterns and algorithmic bias. This study concludes that strengthening the National Work Competency Standards (SKKNI) by explicitly integrating global ethical values is essential to producing IT human resources who are both globally competitive and morally accountable